2018
DOI: 10.1021/acs.jpclett.8b02189
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 1H–1H Distances in Protonated Solids by Frequency-Selective Recoupling at Fast Magic Angle Spinning NMR

Abstract: Nuclear magnetic resonance (NMR) spectroscopy of protons in protonated solids is challenging. Fast magic angle spinning (MAS) and homonuclear decoupling schemes, in conjunction, with high magnetic fields have improved the proton resolution. However, experiments to quantitatively measure 1 H− 1 H distances still remain elusive due to the dense proton−proton dipolar coupling network. A novel MAS solidstate NMR pulse sequence is proposed to selectively recouple and measure interproton distances in protonated samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 39 publications
0
92
0
Order By: Relevance
“…This strategy is feasible only when the magnetization transfer is selective otherwise the other 1 H- 1 H dipolar couplings would complicate this transfer. For example, under a broadband recoupling sequence such as fp-RFDR, the build-up curves show almost similar build-up rates for all 1 H atoms owing to the relayed magnetization transfer [ 40 ]. For this reason, we performed the 1 H- 1 H SERP experiments to selectively transfer the magnetization between a 1 H- 1 H pair, using the sequence in Figure S1d .…”
Section: Resultsmentioning
confidence: 99%
“…This strategy is feasible only when the magnetization transfer is selective otherwise the other 1 H- 1 H dipolar couplings would complicate this transfer. For example, under a broadband recoupling sequence such as fp-RFDR, the build-up curves show almost similar build-up rates for all 1 H atoms owing to the relayed magnetization transfer [ 40 ]. For this reason, we performed the 1 H- 1 H SERP experiments to selectively transfer the magnetization between a 1 H- 1 H pair, using the sequence in Figure S1d .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 lists these distances of the ABZ samples measured from the crystal structure of the forms (CCDC Deposition: 736,654 for ABZ I [24] and CCDC Deposition: 668,711 for ABZ II [23]). The positive contours are the consequence of zero-quantum recoupling happening during the P 0 P 180 P 90 P 270 ( Figure 2) blocks of the constant-time recoupling duration [21]. They give rise to positive cross peaks between adjacent resonances if they are strongly coupled, as shown in Figure 6.…”
Section: Chemical-shift Assignment and Molecular Structurementioning
confidence: 93%
“…The visualisation of 1 H -1 H interactions is particularly useful in small pharmaceutical molecules and reflects on intramolecular, intermolecular, molecular-packing and hydrogen-bonding interactions. Experimental methods such as BASS-SD [20], SERP [21] and 1 H single quantum-double quantum correlation experiments can provide these information [22]. Here, we showed that quantitative 1 H -1 H distances can be measured at fast MAS frequencies using SElective Recoupling of Protons (SERP) experiment.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…SPR is simple, robust and efficient in frequency selective recoupling, which serves as a potential technique to obtain useful restraints for structural determination. It can also be used in a constant-time way to quantitative measurements of distances 31,35 . Compared to the widely-used RFDR, SPR provides sensitivity gains up to 3 for selective 1 H− 1 H correlations (e.g.…”
Section: Figurementioning
confidence: 99%